Alterations in autobiographical memory for a blast event in OEF/OIF veterans with mild TBI - Palombo, D.J. (Neuropsychology, 2015)
OBJECTIVE: Although loss of consciousness associated with moderate or severe traumatic brain injury (TBI) is thought to interfere with encoding of the TBI event, little is known about the effects of mild TBI (mTBI), which typically involves only transient disruption in consciousness. METHOD: Blast-exposed Afghanistan and Iraq War veterans were asked to recall the blast event. Participants were stratified based on whether the blast was associated with probable mTBI (n=50) or not (n =25). Narratives were scored for organizational structure (i.e., coherence) using the Narrative Coherence Coding Scheme (Reese et al., 2011) and episodic recollection using the Autobiographical Interview coding procedures (Levine et al., 2002). RESULTS: The mTBI group produced narratives that were less coherent but contained more episodic details than those of the no-TBI group. CONCLUSIONS: These results suggest that mTBI interferes with the organizational quality of memory in a manner that is independent of episodic detail generation.